Analisis Rantai Pasok Buah Pepaya di Pulau Ambon - Paays, Vilia G; Timisela, Natelda R; Parera, Weldemina B (Universitas Pattimura, 2023)
This study aimed to analyze the mechanism and efficiency of the papaya supply chain in Ambon Island. The analytical method uses qualitative and quantitative analysis. The qualitative analysis describes the mechanism of the papaya supply chain flow, while the quantitative analysis analyzes marketing margins, farmer's share, and marketing efficiency. Based on the results of the analysis, there are 2 supply chain channels for the papaya wulung supply chain in Saniani Maju, the first channel (Producers → Collectors in the mardika market → Consumers), the second channel (Producers → Rujak natsepa traders → Consumers). Papaya bangkok at Gerbang Mas has 1 channel (Farmers → Fris fresh market → Consumers). Analysis of efficiency and farmer share shows that all marketing channels are efficient because they meet the criteria, namely the calculation results of farmer's share ≥ 40% and marketing efficiency value < 50%.